2013
DOI: 10.1007/s00415-013-7169-7
|View full text |Cite
|
Sign up to set email alerts
|

Update on the diagnosis and treatment of neuromyelitis optica: Recommendations of the Neuromyelitis Optica Study Group (NEMOS)

Abstract: Neuromyelitis optica (NMO, Devic’s syndrome), long considered a clinical variant of multiple sclerosis, is now regarded as a distinct disease entity. Major progress has been made in the diagnosis and treatment of NMO since aquaporin-4 antibodies (AQP4-Ab; also termed NMO-IgG) were first described in 2004. In this review, the Neuromyelitis Optica Study Group (NEMOS) summarizes recently obtained knowledge on NMO and highlights new developments in its diagnosis and treatment, based on current guidelines, the publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
467
0
65

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 539 publications
(537 citation statements)
references
References 229 publications
(238 reference statements)
5
467
0
65
Order By: Relevance
“…Acute exacerbations of NMOSD are usually treated with high-dose intravenous (IV) methylprednisolone (IVMP) at a dose of 1000 mg for 3-5 days with or without oral tapering [8,[24][25][26]. It has been shown that each, a first, second, and third course of IVMP significantly improves clinical disability in patients with MS and NMOSD [34], and that early administration is associated with preservation of the retinal nerve fiber layer thickness in NMOSD [35].…”
Section: Treatment Of Nmosd Attacksmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute exacerbations of NMOSD are usually treated with high-dose intravenous (IV) methylprednisolone (IVMP) at a dose of 1000 mg for 3-5 days with or without oral tapering [8,[24][25][26]. It has been shown that each, a first, second, and third course of IVMP significantly improves clinical disability in patients with MS and NMOSD [34], and that early administration is associated with preservation of the retinal nerve fiber layer thickness in NMOSD [35].…”
Section: Treatment Of Nmosd Attacksmentioning
confidence: 99%
“…Several clinical features highly distinctive for NMO and NMOSD have been identified, which include simultaneous LETM and optic neuritis (ON), bilateral ON, and intractable nausea with hiccups and vomiting [7]. Besides clinical evaluation, AQP4-IgG serology and MRI, cerebrospinal fluid diagnostics, evoked potentials, and optical coherence tomography guide diagnosis of NMO and NMOSD [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal cord involvement due to ectopical calcinosis has been observed in only a few cases [112]. In cases where concurrent antiaquaporin 4-positive disease is present, treatment is according to the recommendations of the Neuromyelitis Optica Study Group [113].…”
Section: Sclerodermamentioning
confidence: 99%
“…Prior to the discovery of a serum immunoglobulin G antibody targeting the aquaporine-4 water channel [5,6], it was often considered a variant of multiple sclerosis (MS) as the clinical presentation of these two distinct central nervous system (CNS) diseases may overlap [1]. Indeed, patients with NMOSD are still often misdiagnosed with MS in clinical practice [7,8].…”
Section: Introductionmentioning
confidence: 99%